PERAN KEPALA SEKOLAH SEBAGAI KATALIS PENINGKATAN PRESTASI SISWA - siti hasanah; saddad muzafar; Aril Sandi Noprizal; Khusnul Khotimah; Duwi Kholidatun; Ami Latifah (UNISAN JURNAL, 2023)
The main source of information in this research is the director, who is actively involved on a daily basis. involves educational activities carried out by employees. The purpose of this study is to examine how school principals affect teacher performance at UPT SMPN 24 Bandar Lampung. A descriptive qualitative approach is used in this research method and the information is presented in the form of letters rather than numbers. According to the research results, the principal’s motivational function in improving teachers’ performance was successful because a number of indicators were implemented, such as the arrangement of the physical environment, workplace design, discipline, encouragement, appreciation and provision of Signs include creating learning plans, supervising learning activities, maintaining interpersonal relationships, completing assessments, reviewing assessment results, and mastering the course. This leads to the conclusion that the position of the school principal as a motivator to improve teacher performance is very effective in advancing the quality of learning so that it can encourage the quality of education where performance of teaching staff are the key to success in the world of education.